Lactating Adenoma in Pregnancy: A Case Report - Satrio Sarwo Trengginas; Widyanti Soewoto (HM Publisher, 2022)
Background: Lactating adenoma is a rare palpable breast lesion that occurs late in pregnancy or the lactation period and is commonly found in young primiparous women in the second or third decade of life. This case report aims to describe lactating adenoma and its management. Case presentation: A woman, 24 years old, 26 weeks pregnant, came to the Surgical Oncology Polyclinic of Dr. Moewardi Hospital Surakarta with a complaint of a lump in the right breast from the last 4 months. The lump was felt to be getting bigger, painful to the point that sometimes fluid came out of the nipple of her right breast. The patient had a history of previous lumps with a diagnosis of fibroadenoma that had been operated on. On palpation multiple nodules are palpable. Mammography examination showed a mass with partial calcification (BIRADS 3). The patient was diagnosed with a tumur of mammae dextra suspected of malignant cT2N1Mx with G1P0A0 26 weeks gestation. Histopathological examination results showed a lactating adenoma. Conclusion: There are several recommendations for the management of lactating adenoma during pregnancy. An antepartum biopsy is recommended for women with a breast mass in the first or second trimester, postpartum for masses that appear in the late third trimester, and fine-needle aspiration biopsy as an alternative for masses that appear in the early third trimester. Treatment with bromocriptine, a dopamine agonist, may be given to reduce the size of the lactating adenoma.